Death Anxiety, Immortality Projects and Happiness: A Utilitarian Argument Against the Legalization of Euthanasia - van der Haak, Donovan (Conatus - Journal of Philosophy, 2021)
The current, utilitarian debate on the relation between euthanasia and happiness focusses primarily on the subject of dying patients. Where some utilitarians stress how euthanasia may relieve suffering in the process of dying, others emphasize the importance of respecting the autonomy of others to make decisions like these themselves. However, less attention has been paid to how legalizing euthanasia may impact the human decision-making processes of those still in a healthy and mentally sound state. This paper aims to shed light on this relatively underdeveloped subject within utilitarian theory. In particular, I focus on euthanasia’s most contested form: active, voluntary euthanasia. I draw on Ernst Becker, who argues that moderate death anxiety stimulates people to work on ‘immortality projects,’ decisions that help them cope with the concept of death. Subsequently, I draw on several studies to defend the notion that immortality projects are indirectly conducive to happiness because they stimulate healthy decisions and long-term, human progress. Additionally, immortality projects counterbalance decisions that are based on an excessive drive for short-term pleasure. As euthanasia can make dying less painful, I argue it may diminish death anxiety to significant degree, and thereby also an incentive to work on immortality projects. This brings me to the conclusion that legalizing euthanasia is problematic from a utilitarian point of view, considering the observation that immortality projects are indirectly conducive to happiness.